Infestation, distribution and diversity indices of bruchid species on edible stored pulses in India. (March 2023) - Aidbhavi, Revanasidda; K, Murali Mohan; K R, Soren; Bandi, Sanjay M; M R, Ranjitha; M H, Kodandaram
Abstract: The study aimed to understand the infestation, distribution and, diversity indices of bruchids infesting edible stored pulses in India. A total of 81 stored grain samples representing 14 crops were surveyed from 74 locations across 24 states. Five bruchid species were identified infesting samples, three of which were cosmopolitan Callosobruchus species. C. analis was distributed on 50% of the samples and locations, followed by C. maculatus and C. chinensis . Despite C. analis being present in the majority of samples, C. maculatus was the most abundant and dominant species. Six of the twenty-four states recorded all three Callosobruchus species, eight states recorded any two of the three, and the other ten states recorded any one of the three Callosobruchus species. C. analis and C. chinensis were abundant in four of the six regions, while C. chinensis in NE region. The overall species diversity index was 1.1, while Effective Number of species was 3. C. maculatus was the most abundant and dominant species in small-scale, whereas C. analis in large-scale, storage conditions. Small-scale storages recorded greater diversity and richness, whereas large-scale had greater evenness. Madhya Pradesh, Andhra Pradesh, and Uttar Pradesh states recorded greater diversity indices, whereas West Bengal and Tamil Nadu had lower indices. The maximum diversity indices were found in crops like chickpea ( desi and Kabuli ), and field pea. Small-scale storage conditions recorded higher infestation parameters than large-scale. Field pea, cowpea, chickpea, horse gram, and mungbean recorded higher infestations, while urdbean had the lowest. The order of grain infestation and damage for species was C. chinensis > C. analis > C. maculatus, whereas, it was the opposite for grain weight loss. The grain moisture and storage duration positively correlated with infestation and damage. This study provides vital information on prevailing species diversity and distribution of bruchids on edible stored pulses across the country. Graphical abstract: Image 1 Highlights: Bruchid diversity and distribution on edible stored pulses across India were studied. Five bruchid species were found infesting stored pulses, three of which were cosmopolitan species. Small-scale storages had greater infestations and diversity indices than large-scale storages. The order of infestation and damage by species was C. chinensis > C. analis > C. maculatus . Grain moisture and storage duration positively correlated with infestation and damage.